The Effect of the Thickness of Polycrystalline CdS film on the Efficiency of Cu2S/CdS Solar Cell - Suhail, A. M.; Twej, W. A. A.; Abdulah, S. S.; Saeed, N. M. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this paper, Cu2S/CdS solar cells were prepared with different thickness of CdS layer, these layers were prepared by using chemical spray pyrolysis technique. The chemical spray solution was prepared by mixing cadmium chloride CdCl2 and thiourea CS(NH2)2 of molar concentration 0.1 M/L, the CdS layer was formed after the solution was sprayed on hot Aluminum substrate at temperature 400Â°C. Experimentally the type of CdS film was found as nâ€“type depending on the results of Hall Effect, the value of the Hall factor (RH) is about â€“ 1.348 x 10â€“6 m3/C and the density of the majority charge carriers (N) is about 4.64x1018 cmâ€“3.       The prepared film was tested by using X-Ray diffraction; the result shows that the film was CdS with a polycrystalline structure.       The Cu2S layer was prepared by using Chemical dip process; this layer was formed on the surface of the CdS film and it is always p-type. The heat treatment was utilized to form the pâ€“n junction.      The current-voltage characteristics of p-Cu2S -CdS solar cells was studied, the efficiency of the prepared cells of different thickness; (2.19, 2.52, 3.64, and 5.55) Î¼m of CdS layer was calculated at 85.4 mW/cm2 light intensities, the results show that the thickness of the polycrystalline CdS film is an important parameter affecting the cell efficiency.